دور الحوكمة في تحسين الأداء الاستراتيجي للإدارة الضريبية (Journal of Accounting and Financial Studies ( JAFS ), 2020)
:  The objective of this research is to demonstrate the possibility of applying the principles of corporate governance in the General Authority for taxes, as the goal to identify the basic requirements for the application of the principles of corporate governance in the GCT with an indication of the role of governance in improving the strategic performance of tax administration. The research was based in part applied to the analysis of the results form questionnaire designed to achieve the goal of the research .